From native to cross-platform hybrid development - Pinto, C. M.; Coutinho, C. (Proceedings of the 9th IEEE-TEMS International Conference on Intelligent Systems (IS 2018), 2018)
The current trends towards globalisation, together with the exponential growth of the number of mobile devices led the markets to a boom in the demand for the development of mobile applications. Moreover, with the expansion and heterogeneity of the mobile devices and platforms, software companies need to search for faster and cheaper ways to develop applications that are able to span as many devices as possible in order to capture the market. Currently, Android and iOS Operating Systems roughly share and dominate the mobile market, with timid expressions of other competitors. Each of these mobile operating systems was developed using their own languages and strategy and offer SDKs for development of applications using their libraries – known as native apps. On the other hand, the evolution of HTML5, CSS and JavaScript created generic alternatives to create mobile apps that run on devices on all operating systems, however lacking some capabilities to access the device’s full potential. Alongside came the novel hybrid cross-platform development frameworks, which try to take the best of both worlds. Native versus hybrid platforms the trend in mobile app development using hybrid platforms and their advantage. It would not be great with just one language to develop mobile applications for all mobile devices?